MAINTAINING PATTERNS OF ACTIVITY ENGAGEMENT, COGNITIVE IMPAIRMENT, AND PERCEIVED CONSTRAINTS - Amano, T (Innov Aging, 2018)
Emerging evidence suggests that discrete patterns of activity engagement are associated with various outcomes. However, little is known about changes in patterns of activity engagement and its relationship with cognitive impairment. This study aims to (1) describe changes in patterns of activity engagement and (2) assess whether changes in patterns are associated with cognitive impairment, and (3) examine the moderating role of maintenance of activity on the association between cognitive impairment and perceived constraints. Data came from 2008 and 2012 of the psychosocial questionnaire of the Health and Retirement Study. The final sample consists of 2,815 individuals who aged 65+ in 2008. Latent transition analysis identified five transitional patterns. Result of the OLS regression indicated that interaction between having cognitive impairment and rapid decline in patterns of activity engagement was significant. The finding implies that maintenance of activity pattern is beneficial but further studies are needed to reveal the mechanisms.